PENGARUH PENAMBAHAN LEACHATE TERHADAP TERBENTUKNYA BIO GAS DARI SAMPAH GARBAGE - yuniarno, saudin (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT Leachate is the liquid of the result effect of the rubbish organizing which contain of solution and soft suspension, microba and the rest things as the result of decomposition process. Microba in the leachate can pollute waters and endanger public health. This research used leachete from the material of garbage rubbish. The aim of this research was to know whether the leachate addition can stimulate and optimalize the formation of bio gaz. This research used is the quasi experiment by additing leachate on 5 %, 10 %, and 15 % concentration. Data collection by using primary and secondary data. To know the influence of leachate addition to the time of the forming of bio gaz analyzed by ANOVA. Then research conducted LSD trial, continued LSD trial to the know the difference between control andexperiment group. The result of the research shows that the leachate addition can stimulate and optimalize the forming of bio gaz from garbage rubbish. The leachate addition with 10 %, concentration is the most effective concentration in fastening and the forming bio gaz. For the futur research, the aplication of continued methods has potention to the developed. Key words : leachate, bio gaz, garbage rubbish. Kesmasindo, Volume 7( 1) Juli 2014, Hal 46-53